2022
DOI: 10.1108/bfj-03-2021-0246
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception of clean food labels

Abstract: PurposeThis study puts forth a consumer-oriented concept of clean labels and attempts to empirically investigate consumer perceptions of these labels.Design/methodology/approachA self-administered survey (n = 346) was used as the research instrument for data collection in the current study.FindingsResults from an online survey indicate that consumers perceived less processed, elimination of undesired ingredients and ethical concerns as salient attributes associated with clean labels. Consumer-perceived benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The Institute of Food Technologists (IFT) has proposed a definition: "clean-label means making a product using as few ingredients as possible and making sure those ingredients are items that consumers recognize and think of as wholesome" [11]. Cao and Miao [12] surveyed consumer-perceived clean-label attributes and found that the top three were minimally processed, eliminated undesired ingredients and exercised humane treatment. In order of perceived importance, they were minimally processed, had familiar ingredients, eliminated undesired ingredients, used local ingredients, and demonstrated an absence of allergens [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Food Technologists (IFT) has proposed a definition: "clean-label means making a product using as few ingredients as possible and making sure those ingredients are items that consumers recognize and think of as wholesome" [11]. Cao and Miao [12] surveyed consumer-perceived clean-label attributes and found that the top three were minimally processed, eliminated undesired ingredients and exercised humane treatment. In order of perceived importance, they were minimally processed, had familiar ingredients, eliminated undesired ingredients, used local ingredients, and demonstrated an absence of allergens [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, soda beverage manufacturers may combine polyols with high-intensity sweeteners such as aspartame, acesulfame K, or neotame to reduce the polyol concentration while still ensuring sufficient perceived sweetness. However, some high-intensity artificial sweeteners induce glucose intolerance by altering the gut microbiota ( Suez et al, 2014 ); further, this approach goes against a growing trend among food manufacturers toward “clean labeling” with shorter lists of ingredients ( Asioli et al, 2017 ; Cao & Miao, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food additives are important ingredients in many processed food and beverages, yet this ingredient is controversial to be used due to consumer concerns [1,2]. Food with "additive" labels may bring a negative perception in consumers' minds mainly due to "food safety" and "healthy" reasons [1,2]. In a consequence, this decreases consumers' trust in food with the "additive" labels on the packaging [3].…”
Section: Introductionmentioning
confidence: 99%
“…Around 60% of global respondents avoid having artificial flavours in their products and prefer the presence of natural flavour [5]. According to a study by Breath et al [1], the use of artificial flavours in food and beverages is decreased as consumers gravitate towards options that they perceived as more natural and clean labels [2]. The previous report using Western consumers from North America and Europe as their subjects revealed that food products without artificial flavour are considered more important and was able to drive purchase interest [5,6] indicating that the use of natural and artificial flavours in food can shift consumer preferences in their decision to buy and to consume foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation